2016
DOI: 10.1016/j.ijproman.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Taming the ‘trolls’: Major public projects in the making

Abstract: Major projects are not yet sufficiently understood, and practices in project governance and project management do not yet reflect the current state of knowledge of large, complex projects. In an attempt to understand the reasons, the authors therefore investigated the latest relevant findings documented in three countries: the UK, Norway, and the Netherlands. Their examination of the effect of implementing governance frameworks for public projects in these countries indicates that efforts to improve major proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
0
67
0
1
Order By: Relevance
“…Studies have also advanced beyond the organisational level, and involved analyses of the global context of large projects (Scott et al 2011), the national institutional context hosting projects (Sydow & Staber 2002;Grabher 2002), and their related social networks (Manning & Sydow 2011), within and beyond organizations directly engaged in projects (Morris & Geraldi 2011;) and the nature of so-called interinstitutional projects (Dille & Söderlund 2011), and alternative approaches to guide their complex relationships (Walker & Lloyd-Walker 2015;Bresnen 2010). The latter highlights the fact that projects often span institutional boundaries, regulatory frameworks (Klakegg et al 2015), and organizational fields, which make it difficult for projects to uphold all-embracing legitimacy for what to produce, how to produce it, when to produce it, and who to involve (Brady et al 2006). Problems that have been identified, but not yet fully understood, and where project scholars can make significant contribution to policy.…”
Section: Ten Years Aftermentioning
confidence: 99%
“…Studies have also advanced beyond the organisational level, and involved analyses of the global context of large projects (Scott et al 2011), the national institutional context hosting projects (Sydow & Staber 2002;Grabher 2002), and their related social networks (Manning & Sydow 2011), within and beyond organizations directly engaged in projects (Morris & Geraldi 2011;) and the nature of so-called interinstitutional projects (Dille & Söderlund 2011), and alternative approaches to guide their complex relationships (Walker & Lloyd-Walker 2015;Bresnen 2010). The latter highlights the fact that projects often span institutional boundaries, regulatory frameworks (Klakegg et al 2015), and organizational fields, which make it difficult for projects to uphold all-embracing legitimacy for what to produce, how to produce it, when to produce it, and who to involve (Brady et al 2006). Problems that have been identified, but not yet fully understood, and where project scholars can make significant contribution to policy.…”
Section: Ten Years Aftermentioning
confidence: 99%
“…e active citing document discussed how challenges of megaprojects were resolved through the right governance structure [69]. Governance of megaprojects is extremely complex due to the complex context, such as changing teams and organizational cultures [50].…”
Section: Analysis Of Cocitation Clustersmentioning
confidence: 99%
“…Ng et al (2012) pointed out that public participation should be allowed by the government throughout the whole project lifecycle, which has been usually ignored yet (Xie et al, 2017). To improve the transparency in managing megaprojects, World Bank (2016)suggested that the government should release important information of megaprojects opportunely and regularly, such as taking the media as a governance mechanism (Bednar, 2012), and establishing agency to audit and assess performance of megaprojects (Klakegg et al, 2016).…”
Section: Governmental Governance In Megaprojectmentioning
confidence: 99%
“…In The United Kingdom, government plays a major role in supervising megaprojects. For instance, the Office of Government Commerce will establish guidelines for megaproject implementation; the Major Project Authority needs to report the construction status annually; and the National Audit Office is responsible for reviewing the report (Klakegg et al, 2016). Despite the increasing adoption of governmental governance, few studies have been done to examine the interrelationships between governmental governance and megaproject performance.…”
Section: Introductionmentioning
confidence: 99%